Effect Of Water Restriction On Physiological Responses Of Indigenous Hoggets In Middle Gujarat Agro Climatic Condition - Patel, N.R.; Islam, M.M.; Modi, R.J.; Wadhwani, K.N. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Eighteen farm born unshorn hoggets (25-30 kg) of Patanwadi and Marwari breeds of sheep were selected and randomly divided into three treatment groups on the basis of body weight comprising of six in each group, viz., T1: Control (ad.lib. water), T2: (WR1-20% water restriction), T3: (WR2- 40% water restriction) to study the effect of water restriction (WR, for 28 days) on physiological responses. The experimental animals under T3 showed significantly (P
Keywords: Water restriction; physiological responses; Hoggets; Middle Gujarat